2018
DOI: 10.1159/000493547
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Internal Neurolysis for Trigeminal Neuralgia without Neurovascular Compression and Its Relationship with Intraoperative Trigeminocardiac Reflex

Abstract: Background: Internal neurolysis (IN) is an effective surgical treatment for trigeminal neuralgia (TN) without neurovascular compression (NVC) or postoperative recurrence. However, the trigeminal nerve is directly manipulated during the procedure, and there is a high incidence of trigeminocardiac reflex (TCR). The aim of this study was to retrospectively analyze the outcome of IN and to explore its relationship with the occurrence of intraoperative TCR. Methods: Surgical and anesthesia records of 27 TN patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…X.-F.J. and M.W. together, which had been published previously in detail by our team [15]. Both intraoperative findings and postoperative review of operative video were used to confirm the diagnosis of wNVC TN or woNVC TN prospectively.…”
Section: Mvd and Inmentioning
confidence: 99%
“…X.-F.J. and M.W. together, which had been published previously in detail by our team [15]. Both intraoperative findings and postoperative review of operative video were used to confirm the diagnosis of wNVC TN or woNVC TN prospectively.…”
Section: Mvd and Inmentioning
confidence: 99%
“…17,18 Also about 90% of patients suffered from facial numbness after MVD combined with internal neurolysis. [19][20][21] Complications could also impact the life quality of the patients. Zhang et al compared the effect and complications of redo MVD and percutaneous radiofrequency thermocoagulation for TN with failed MVD, the result showed that re-do MVD had better pain control and less complication.…”
Section: Discussionmentioning
confidence: 99%
“…The most common complication of MVD combined with IN is ipsilateral numbness [ 10 , 19 , 20 ]. Most of the patients in this group (88.6%) had different degrees of facial numbness on the surgical side after operation, which was much higher than that after MVD alone (10.3%) ( p <0.01).…”
Section: Discussionmentioning
confidence: 99%